When social forces remove the impact of competition: Social exchange in experimental labor markets - Ernst Fehr; Erich Kirchler; Andreas Weichbold (Institute for Advanced Studies (IHS), 1995)
Do competitive markets remove the impact of social norms and customs on market out-comes? Or are these social forces capable of exerting a persistent influence? Many economists seem to believe that social norms and customs have, if at all, only temporary effects in competitive markets. So far this belief has been confirmed by the evidence of many competitive market experiments. In this paper we report the results of a series of competitive market and bilateral bargaining experiments. They indicate that social norms may not only persist in a competitive environment but that they may completely remove the impact of competition on the market outcome. – – Bewirken kompetitive Märkte, daß soziale Normen und Gewohnheiten im Markt verschwinden? Oder können diese sozialen Einflüsse einen dauerhaften Einfluß auf das Marktgeschehen ausüben? Viele Ökonomen glauben, daß soziale Normen und Gewohnheiten höchstens einen nicht dauerhaften Einfluß ausüben. Viele kompetitive Marktexperimente haben bis jetzt Evidenz für diesen Glauben geliefert. In dieser Arbeit berichten wir über Resultate in einer Reihe von kompetitiven Markt- und bilateralen Verhandlungsexperimenten. Die Resultate zeigen, daß soziale Normen in einem kompetitiven Rahmen nicht nur erhalten bleiben, sondern daß sie den Einfluß kompetitiven Verhaltens auf das Marktergebnis ausschalten.
Keywords: C91; C92; J30; J31; J41; 330; competition; social exchange; trust; reciprocity; social norms